Episcleral spread of ciliochoroidal melanoma following surgeries: a case report - E.E. Grishina; I.D. Kim; E.N. Izotova (РМЖ "Клиническая офтальмология")
E.E. Grishina, I.D. Kim, E.N. Izotova M.F. Vladimirskiy Moscow Regional Research and Clinical Institute, Moscow, Russian Federation Uveal melanoma is one of the most aggressive malignant tumors because its metastasis occurs by hematogenous spread. As a rule, a large tumor size and its extrascleral extension are associated with poor survival prognosis. Uveal melanoma may masquerade as other eye disorders, creating difficulties for making diagnosis and initiating timely treatment. The article presents a clinical report of ciliochoroidal melanoma with a large episcleral nodule and orbital extension through the optic nerve, stage T4N0M0. The initial diagnosis was wrong, and, as a result, the patient received inadequate treatment for a long period of time. Follow-up of the patient with the misdiagnosis of benign eye disease continued for 20 years. The cataract and glaucoma surgeries were carried out. However, the patient still had persistent elevation of intraocular pressure. The misdiagnosis was underpinned by a lack of oncologic alert and an incomplete set of used clinical and instrumental methods. Ultimately, it was necessary to perform the left orbital exenteration. The disrupted eye globe integrity caused by the glaucoma surgery and cataract extraction contributed to the extrascleral tumor growth. The inadequate therapy and delayed anti-tumor treatment of uveal melanoma necessitated to increase the scope of the surgical excision — the left orbital exenteration and, potentially, could deteriorate the survival prognosis. Keywords: uveal melanoma, ciliochoroidal melanoma, secondary ophthalmic hypertension, extrabulbar extension of uveal melanoma, diagnostic errors. For citation: Grishina E.E., Kim I.D., Izotova E.N. Episcleral spread of ciliochoroidal melanoma following surgeries: a case report. Russian Journal of Clinical Ophthalmology. 2023;23(2):107–110 (in Russ.). DOI: 10.32364/2311-7729-2023-23-2-107-110.